Awareness and Knowledge of the Sustainable Development Goals Among Elderly People of Balangir Town, Odisha - Pati, Jyotirmayee (Integrated Journal for Research in Arts and Humanities, 2022)
The sustainable development usually means the development of economic growth without harming natural resource. The survey is conducted on urban area of Balangir taking 15 elderly people asking each of them about 70 questions about how much they aware with the word sustainable development and it’s impact on today’s generation with growing population. Then the individual response is recorded which include both positive and negative response is also included. Then a single pie chart for each people is obtained according to their responsibility.